EVALUATION OF TOPICAL ANTI-WRINKLE AND FIRMING (AWF) FOR WOMEN, ANTI-WRINKLE AND FIRMING (AFM) FOR MEN AND DEEP WRINKLES FOR WRINKLES ON FACE AND NECK - S, Arsiwala; S, Tahiliani; h, Jerajani; BS, Chandrashekhar; S, Aurangabadkar; M, Kohli; P, Savardekar; K, Sarangi; RD, Kharkar; F, Shah (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Abstract Wrinkles are the clinical manifestation of ‘cutaneous aging'. ‘Anti-Wrinkle and Firming (AWF) for Women', ‘Anti-Wrinkle and Firming (AWF) for Men' is an Integral Correction Serum specifically for woman and man for the treatment of fine wrinkles. Deep Wrinkles' is an Integral Correction Serum that significantly reduces the appearance of deep wrinkles. An open labelled, prospective, multi-centric clinical study was conducted to determine the efficacy, safety &quality of life parameters with ‘AWF for Women', ‘AWF for Men' and ‘Deep Wrinkles' in the treatment of fine to deep wrinkles on face and neck in 30 patients (10 patients in each group) for 12 weeks. The patients were assessed for Modified Fitzpatrick Wrinkle Scale (MFWS), improvement in ‘Quality of Life', ‘Patient Satisfaction Questionnaire', Physician's and Patient Global Assessment Grade for improvement in wrinkles and Photographic assessment at baseline, 6 weeks and 12 weeks. The average MFWS at baseline was 1.8, 2.1, and 2.7 which was reduced to 1.1, 1.6, and 2.1 after 12 weeks of treatment with AWFW, AWFM and Deep Wrinkles respectively. Average grade for Physician's global assessment improved from 1, 1, and 1 at baseline to 2.1, 2.6, and 2.7 at the end of 12 weeks treatment. Patient's global assessment also showed similar grades of improved from 1, 1, and 1 at baseline to 2, 2.7, and 2.2 at the end of treatment with AWFW, AWFM and Deep Wrinkles respectively. There was an overall improvement in ‘Quality of Life' in terms of improvement in the wrinkles at the end of 6 weeks (Grade 2.6, 2.5, 2.3) and 12 weeks (Grade 2.9, 2.9, 2.7) at the end of treatment with AWFW, AWFM and Deep Wrinkles respectively. The overall ‘Patient Satisfaction' was found to be good at the end of 12 weeks of treatment (Grade 2.5, 2.5, 2.5) with AWFW, AWFM and Deep Wrinkles respectively. Of the thirty patients, 1 patient for AWFW, 1 patient for AWFW and 2 Patients on ‘Deep Wrinkle' complained of the adverse events like burning sensation. The results of this study show that AWF for Women, AFM for Men and Deep Wrinkles (DW) have a good potential for the treatment of wrinkles. Key words: Anti-Wrinkle and Firming (AWF) for Women, Anti-Wrinkle and Firming (AWF) for Men, Deep Wrinkles, Wrinkles, Modified Fitzpatrick Wrinkle Scale (MFWS)